Driving youngsters to be green: The case of plant-based food consumption in Indonesia. (20th December 2022) - Suhartanto, Dwi; Kartikasari, Ani; Arsawan, I Wayan Edi; Suhaeni, Tintin; Anggraeni, Tiara
Abstract: Environmental degradation and the rising popularity of healthy, sustainable diets have increased public awareness of the importance of plant-based food (PBF). This creates opportunities for unique business development, and comprehending strategies to strengthen consumers' favorable green attitude and behavior is crucial. Youngsters embrace this shift in food choice. This study aims to provide a holistic understanding of the formation of attitude and behavioral intention toward PBF by integrating consumption value, environmental concern, and perceived cost as the drivers, as well as assessing the gender moderating role. Data was gathered through online questionnaires from 334 young green customers from Indonesia's greater Jakarta region. Using partial least squares for data analysis, this study reveals that environmental concern, and the functional, social, and conditional values are significant predictors of attitude and behavioral intention. Further, this research shows that gender does not moderate the association between attitude and behavioral intention, and its drivers. These findings provide guidance for PBF business managers to improve their competitiveness and, at the same time, contribute toward a more sustainable environment.